2021
DOI: 10.20885/jaai.vol25.iss1.art4
|View full text |Cite
|
Sign up to set email alerts
|

An analysis on fraud tendency of village government officials

Abstract: This research aims to analyze the influence of information asymmetry, religiosity, organizational culture, and regulatory enforcement toward fraud tendency of village government officials. This study employed a survey approach as the method to obtain data. Regression analysis was used to test the proposed hypotheses. From seventy-one respondents working as village government administrators in thirty-five villages in Magetan Regency, East Java Province, this study has found that information asymmetry, religiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In 2022, the KPK caught eight regional heads red-handed in corruption cases, including the mayors or regents of the cities or districts of Bekasi, North Penajam Paser, Langkat, South Buru, Bogor, Ambon, Yogyakarta, and Pemalang (Sahlan & Bunaiya, 2022). Previous research showed that fraud and corruption are incurred in several government institutions not just at the central and local government level but also at the village government level (Dewi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, the KPK caught eight regional heads red-handed in corruption cases, including the mayors or regents of the cities or districts of Bekasi, North Penajam Paser, Langkat, South Buru, Bogor, Ambon, Yogyakarta, and Pemalang (Sahlan & Bunaiya, 2022). Previous research showed that fraud and corruption are incurred in several government institutions not just at the central and local government level but also at the village government level (Dewi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%